Older Workers and Affective Job Satisfaction: Gender Invariance in Spain - Fernández-Muñoz, Juan J.; Topa, Gabriela (Frontiers in Psychology, 2018)
Older employees’ affective job satisfaction is an aspect that arouses growing interest among researchers. Among the affective measures of job satisfaction, the Brief Index of Affective Job Satisfaction (BIAJS) is one of the most used in the last decade. This study is intended to the test the gender invariance of the BIAJS in two samples of workers over age 40 in Spain. The first sample, of 300 participants and the second sample, of 399 participants, have been used to test gender invariance of the BIAJS. In comparison with the original English version, the Spanish version of the BIAJS has adequate psychometric properties. The findings allow us to consider it a valid and reliable tool to assess older people’s affective expressions about their work. In addition, this study provides evidence of its factorial invariance as a function of gender.